Influence of Pre- and Postharvest Summer Pruning on the Growth, Yield, Fruit Quality, and Carbohydrate Content of Early Season Peach Cultivars - Ali Ikinci (The Scientific World Journal)
Winter and summer pruning are widely applied processes in all fruit trees, including in peach orchard management. This study was conducted to determine the effects of summer prunings (SP), as compared to winter pruning (WP), on shoot length, shoot diameter, trunk cross sectional area (TCSA) increment, fruit yield, fruit quality, and carbohydrate content of two early ripening peach cultivars (“Early Red” and “Maycrest”) of six years of age, grown in semiarid climate conditions, in 2008 to 2010. The trees were grafted on GF 677 rootstocks, trained with a central leader system, and spaced 5 × 5 m apart. The SP carried out after harvesting in July and August decreased the shoot length significantly; however, it increased its diameter. Compared to 2009, this effect was more marked in year 2010. In general, control and winter pruned trees of both cultivars had the highest TCSA increment and yield efficiency. The SP increased the average fruit weight and soluble solids contents (SSC) more than both control and WP. The titratable acidity showed no consistent response to pruning time. The carbohydrate accumulation in shoot was higher in WP and in control than in SP trees. SP significantly affected carbohydrate accumulation; postharvest pruning showed higher carbohydrate content than preharvest pruning.